Transformation and Development Trend of Enterprise Digital Marketing Driven by AR Technology - Pang, Zitong (Transactions on Economics, Business and Management Research, 2024)
Augmented reality (AR) is a technology that overlays virtual information onto the real-world environment in order to enhance users’ perception and experience of the physical world. With advancement of technology, AR technology is gradually permeating into all domains of enterprise digital marketing, triggering a profound transformation. Enterprises have explored the application potential of AR technology in marketing, product display, customer service, and other fields, aiming to achieve the transformation and upgrading of the business model and the enhancement of market competitiveness through this innovative technology. This study will elaborate in detail on how AR is being utilized in the digital marketing strategies of various enterprises and the future trends of this transformation. Through the collection of data, case studies, and analysis of user behavior from multiple companies, it was discovered that this technology not only enhances the interactive experience of customers but also facilitates a profound connection between brands and consumers. The results of this study further demonstrate that enterprise digital marketing driven by AR technology is evolving towards a more individualized and immersive direction, presenting unprecedented business opportunities for enterprises.